Prácticas alimentarias en niños y adolescentes con síndrome de Down que asisten a las Escuelas Especiales N° 1 y 2 y CADE de la ciudad de Loja periodo enero-junio del 2016. - Cueva Loaiza, Adriana Malena (2017)
Down syndrome (DS) is a very common genetic disease, low stature; overweight and obesity are typical of the syndrome and constitute a health problem because of the disorders they generate, for this reason the research work was proposed, which objective was to identify the alimentary practices in children and adolescents with SD who attend the special schools N ° 1, 2 and the CADE of the city of Loja during the period January-June of 2016. The present study was descriptive-cross-sectional, both a survey and an anthropometric measurement were conducted, with a sample of 30 participants (17 men and 13 women); it was obtained that from the alimentary practices: Healthy 100% were integrated into the meal with the family and 33% unhealthy eating very often watching television. The frequency of food consumption showed that 77% frequently consume farinaceous foods and not very frequent in 53% protein foods. Daily servings of farinaceous foods are increased for age, and rations of protein foods are insufficient, as well as dairy products, fruits and vegetables that predominate in the group of adolescents. All children and adolescents are integrated into the meal with the family and eat watching television, very often they consume farinaceous foods in rations that are increased for the age, contributing more to the overweight and obesity. Key words: Down syndrome, alimentary practices, nutritional status, overweight, obesity.